Politicity and Proportionality as Methods for Resolving Collisions of Constitutional Values - Korycka-Zirk, Milena (Teisė, 2023)
From a philosophical-legal point of view this article examines the polarisation of the politico-legal discourse between liberal constitutionalism and the concept of the primacy of the integrity of the constitution, which from the perspective of modern constitutionalism is identified with the possible use of two different methods of resolving collisions of constitutional values – the proportionality test and the politicity test.